Efeito da substituição parcial do farelo de soja por feno ou silagem de gliricídia na dieta de cordeiros confinados - Lemos, Antônio José (2015)
The objective was evaluate the effect of partial replacement of soybean meal for hay or silage of gliricídia in feedlot lambs on the terminate fase for performance, carcass characteristics and feeding behavior. Were used 18 male lambs, not castred, with approximately 120 days of age and average body weight of 21 ± 2.2 kg. The experimental design was completely randomized with three treatments and six replications. The lambs were keep in confinement and subimitted to the following diets: Control Diet (CONT) diet based in elephant grass hay (Pennisetum purpureum) + corn meal + soybean meal; Gliricídia Hay (HGLI) diet formulated for replacing 57.4% of soybean meal by Gliricidia sepium Hay; Gliricídia Silage (SGLI) - diet formulate for replacing 57.4% of soybean meal for Gliricidia sepium Silage. The weight of the animals were held every two weeks and daily were used leftovers and water supply, food remains in the trough and feed supply, keeping an ample percentage in the trough of 15%. The feeding behavior of the animals was determined in three stages: beginning, middle and end of the experiment for 24 hours/day, in a 5 minute intervals to determine the time spent in eating, ruminating and idling. To obtain the average number of ruminating chews and the time taken by chewing, the observations were made, per animal, four ruminal bolus at different times of day (09:00 to 11:00, 15:00 to 17:00 and 20:00 to 22:00). Lambs were slaughtered after completing 75 days of confinement with average body weight of 26.46; 32.80 and 32,30kg for animals submitted to the treatments CONT, HGLI and SGLI respectively. The DM, CP, NDF and ADF were higher (P <0.05) for the HGLI treatment and did not differ (P> 0.05) between CONT and SGLI treatments. Feed intake of NDT differ (P <0.05) among treatments. Water intake differ (P <0.05) among the three treatments being higher for HGLI following the CONT and SGLI. Had difference (P <0.05) average daily gain, live weight at slaughter, empty body weight, hot and cold carcass weight, were higher for HGLI and SGLI treatments. The feed conversion differed (P <0.05) between CONT and SGLI treatments. There was no difference (P> 0.05) for the variables yield hot and cold carcass, real income and fat thickness. There was no difference (P> 0.05) between the behavior parameters of feed intake, rumination, total chewing time and leisure. The feeding and rumination efficiency in g DM and NDF/hour were higher for HGLI treatment. The number of ruminating chews (number/day) was higher for HGLI and SGLI treatments, however, does not difference (P> 0.05) between HGLI and CONT treatments. The number of chews (numbers/bolus) and the chewing time (sec) per bolus for were higher (P <0.05) for CONT and HGLI treatments. The number of ruminated bolus (number/day) was higher to the SGLI treatment. It can be concluded that the partial replacement of soybean meal for hay or silage of gliricídia gave a positive effect on performance and carcass characteristics of feedlot lambs.